2019
DOI: 10.1016/j.pvr.2019.100171
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination in Papua New Guinea to prevent cervical cancer in women: Gender, sexual morality, outsiders and the de-feminization of the HPV vaccine

Abstract: Papua New Guinea has among the highest estimated burden of cervical cancer globally, but currently lacks national cervical screening or human papillomavirus (HPV) vaccination programmes. The Papua New Guinean government is committed to introducing the HPV vaccine for primary prevention, but locally-relevant research evidence is not available to guide implementation. Experience from earlier Papua New Guinean health programmes suggests that appropriate engagement with local health cosmologies and cultures for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…These beliefs were particularly evident when concepts of cultural taboo were brought forth. For instance, despite overall support for vaccination in a community in Papua New Guinea, there were concerns expressed by community members about a perceived increase in promiscuity once disease protection was acquired from the HPV vaccine; some participants believed that there might be a community-wide increase in the sex trade [32]. In settings where public health messaging focused on the sexually transmitted nature of HPV, healthcare providers suggested that explicit discussions about sex were needed; such discussions was seen as problematic by Indigenous community members where cultural taboos about discussing matters related to sex, such as sexually transmitted infections (STIs), may persist (e.g., from cultural or historical factors).…”
Section: Thematic Barriers To Hpv Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…These beliefs were particularly evident when concepts of cultural taboo were brought forth. For instance, despite overall support for vaccination in a community in Papua New Guinea, there were concerns expressed by community members about a perceived increase in promiscuity once disease protection was acquired from the HPV vaccine; some participants believed that there might be a community-wide increase in the sex trade [32]. In settings where public health messaging focused on the sexually transmitted nature of HPV, healthcare providers suggested that explicit discussions about sex were needed; such discussions was seen as problematic by Indigenous community members where cultural taboos about discussing matters related to sex, such as sexually transmitted infections (STIs), may persist (e.g., from cultural or historical factors).…”
Section: Thematic Barriers To Hpv Vaccinationmentioning
confidence: 99%
“…Some Indigenous people in the literature were uneasy about the possibility of infertility or sterilization. Community participants in Papua New Guinea feared that the HPV vaccine would result in the destruction of reproductive organs and trigger additional complications resulting in infertility [32]. Other studies echoed concerns about infertility arising from the vaccine [41,45].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Thus, more and more attention has been paid to the early screening of cervical diseases in clinical practice, and more effective and reasonable examination methods have been developed to improve the accuracy of cervical disease diagnosis (21). Cervical cancer is the only gynecological cancer that can be diagnosed early and cured, and the early detection of pre-cancerous lesions is the key link in the prevention and treatment of cervical cancer (22)(23)(24)(25). Traditional cervical cancer screenings are aimed at the early detection of cervical cancer, while modern cervical cancer screenings are aimed at the early detection of high-grade CIN lesions and the early treatment of obstructive cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Following the teachings of Freire and Boal, the use of theatre to educate, liberate and give community a voice to discuss specific concerns and health challenges can highlight information gaps and provide insight into how health information can be customised to address community needs [ 57 ]. In PICTs, where quality health information is often unavailable, communities rely on stories to make decisions regarding health behaviour [ 62 ]. According to Silver [ 56 ], storytelling as a method to effect health behaviour change requires only imagination and understanding of the cognitive frame of a particular community.…”
Section: Discussionmentioning
confidence: 99%